2013
DOI: 10.1177/0954407012467289
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the flow-induced sunroof buffeting noise of a simplified cavity model based on the slightly compressible model

Abstract: Numerical computation was conducted to investigate the flow-induced sunroof buffeting noise at low Mach numbers. In order to avoid the stiffness problem which occurs in solving the compressible fluid equations at low Mach numbers, new governing equations were derived with the assumption that there is a slight compressibility effect. The mechanisms of the flow-induced sunroof buffeting noise were investigated by considering a three-dimensional model cavity. Extensive wind tunnel tests were conducted to verify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Through the logarithmic operation to the sound pressure after the FFT operation, the sound pressure level result of the monitoring point can be obtained: SPL(dB) = 10 log 10 P( f ) P re f 2 (7) where P ref is the reference sound pressure related to the minimum sound pressure amplitude that can be heard by a human, and the value is 2 × 10 −5 Pa.…”
Section: Acoustic Post Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the logarithmic operation to the sound pressure after the FFT operation, the sound pressure level result of the monitoring point can be obtained: SPL(dB) = 10 log 10 P( f ) P re f 2 (7) where P ref is the reference sound pressure related to the minimum sound pressure amplitude that can be heard by a human, and the value is 2 × 10 −5 Pa.…”
Section: Acoustic Post Processingmentioning
confidence: 99%
“…Oettle [6] used the Lattice Boltzmann method to evaluate the sunroof buffeting characteristics of a specific model of a vehicle, and the suppressing effect of the spoiler with or without the grid on the sunroof buffeting characteristics was analyzed. Wang [7] studied the mechanism of the sunroof buffeting noise at the speed of low Mach numbers based on a three-dimensional cavity model. The results showed that airflow separation, vortex shedding, vortex impact, periodic pressure wave feedback, and Helmholtz resonance are responsible for sunroof buffeting.…”
Section: Introductionmentioning
confidence: 99%
“…The simple model acoustic wind tunnel test was completed in the US Purdue University Herrick Low Noise Wind Tunnel. 21,22 The wind tunnel is a direct current, low speed, single test section acoustic wind tunnel, the length of the wind tunnel is 10.4 m, the total height is 2.3 m, the length of the wind buffeting noise test section is 1.23 m, the width of the test section is 0.53 m, and the height is 0.58 m. The test wind speed was set at 25 m/s. Figure 3 shows the cavity model and its installation.…”
Section: Wind Tunnel Test Verifies the Accuracy Of Ilrn And Des-ilrn mentioning
confidence: 99%
“…During the last several years, some studies on buffeting were carried out by Gu et al, with part of the study focused on numerical investigations of automobile side window buffeting (Yang et al, 2014; Gu et al, 2015) and the other part of the study focused on numerical and experimental studies of 3D sunroof-like cavity buffeting (Wang et al, 2012, 2013). Based on a 3D sunroof-like cavity, numerical simulations were conducted at various velocities and showed good agreement with the wind tunnel measurements.…”
Section: Introductionmentioning
confidence: 99%